(untitled) (Journal of Scientific Research, 2020)
This paper reports the refractive indices ( ) of N,N-diethylethanamine + methyl acetate, ethyl acetate, propyl acetate, butyl acetate and pentyl acetate at 298.15 K and at different composition range. The various empirical correlations like Arago-Biot (AB), Gladstone-Dale (GD), Lorentz-Lorenz (L-L) Heller (H), Weiner (W), Newton (Nw) and Erying-John (E-J) were applied to experimental data for estimating theoretical value of refractive indices. For an equimolar mixture, the predicted deviation in refractive index values is consistent well with the experimental data. It has been found that the interactions between amine and different esters decrease when carbon chain length in ester increases. Also refractive indices are affected with change in temperature. To evaluate the standard deviation, RK polynomial equation was fitted to the measured refractive indices data.